2009
DOI: 10.1017/s1461145709990630
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute and repeated citalopram in mouse models of anxiety and depression

Abstract: Clinically, SSRIs are widely prescribed in the treatment of several anxiety disorders, though very few pre-clinical studies have observed a beneficial effect of this class of drugs in animal models of anxiety. Furthermore, the biphasic pattern observed clinically, an exacerbation of anxiety followed by beneficial effects, is rarely observed in animal studies. In the present study we document this clinical phenomenon in several behavioral paradigms. While a single injection of citalopram induced anxiogenic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 58 publications
5
37
2
Order By: Relevance
“…The pronounced anxiolytic-like action of citalopram observed in the EZM contrasts with earlier reports in mice. Previous studies reported either anxiogenic-like or no effects of acute SSRI treatment in the mouse EPM and EZM (Borsini et al, 2002;Kurt et al, 2000;Mombereau et al, 2010). To our knowledge this is the first demonstration of anxiolytic-like action of acute SSRI treatment in the mouse EZM or EPM.…”
Section: Discussionsupporting
confidence: 48%
“…The pronounced anxiolytic-like action of citalopram observed in the EZM contrasts with earlier reports in mice. Previous studies reported either anxiogenic-like or no effects of acute SSRI treatment in the mouse EPM and EZM (Borsini et al, 2002;Kurt et al, 2000;Mombereau et al, 2010). To our knowledge this is the first demonstration of anxiolytic-like action of acute SSRI treatment in the mouse EZM or EPM.…”
Section: Discussionsupporting
confidence: 48%
“…Preskorn 1996;Anderson et al 2002), in contrast to acute and subchronic studies (e.g. Aznavour et al 2006;Beyer and Cremers 2008;Mombereau et al 2010). Further, chronic administration of an SSRI in healthy participants leads to changes in behaviour, mood, personality and brain function, consistent with augmented serotonergic function (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is evidence that this is not the case (e.g. Jensen et al 1999;Burghardt et al 2004;Beyer and Cremers 2008;Mombereau et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SSRIs represent one of the most widely used classes of drugs for psychiatric disorders. One limitation of SSRIs is that acute administration can lead to negative behavioral states1,2, a finding that is recapitulated in rodent models3,1620. Importantly, the BNST has been demonstrated to be an anatomical site of action for some of the aversive actions of SSRIs in rodents4.…”
mentioning
confidence: 99%